Receptor Subtypes Mediating the Inotropic Effects and Ca2+ Signaling Induced by Endothelin-1 Through Crosstalk With Norepinephrine in Canine Ventricular Myocardium - Li Chu; Jian-Xin Zhang; Ikuo Norota; Masao Endoh (Elsevier, 2005)
In canine ventricular myocardium, endothelin-1 (ET-1) alone induced only a weak transient negative inotropic effect (NIE). However, ET-1 induced a marked sustained positive inotropic effect (PIE) subsequent to a transient NIE in the presence of norepinephrine (NE) at low concentrations (0.1 - 1 nM) and elicited a pronounced sustained NIE in the presence of NE at high concentrations (around 100 nM). Thus, the extent of β-adrenoceptor stimulation induced by NE played a crucial role in determining the characteristics of the inotropic effects of ET-1. The characteristics of ET receptor subtypes involved in contractile regulation and Ca2+ signaling induced by ET-1 were determined. The ET-1-induced transient NIE and decrease in Ca2+ transients were abolished by the selective ETA-receptor antagonist FR319317, but not by the selective ETB-receptor antagonist BQ-788. The sustained PIE and the increase in Ca2+ transients induced by ET-1 were abolished by FR319317, but not inhibited by BQ-788. In contrast, the sustained NIE of ET-1 was abolished by the non-selective ET antagonist TAK-044, markedly attenuated by FR319317, and partially inhibited by BQ-788. ET-1 alone elicited a PIE in the presence of BQ-788, which indicates that the activation of ETB-receptors counteracts the development of the PIE of ET-1. The current findings indicate that both ETA and ETB receptors are involved in the regulation of Ca2+ signaling and contractility in canine ventricular myocardium. Keywords:: inotropic effect, endothelin receptor subtype, endothelin-1, norepinephrine, canine ventricular myocardium